MENINGKATKAN MINAT BELAJAR MENGHAFAL DOA DENGAN METODE BERCERITA ANAK USIA 5-6 TAHUN DI TK BAROKAH PEKANBARU - Putri Clawson; Sri Haryanti (Jurnal Ta'lim : Journal Ilmu Pendidikan dan Ilmu Keguruan, 2018)
This study aims to obtain data on children's prayer interest reading through storytelling methods at Barokah Kindergarten Pekanbaru. The research method used is Classroom Action Research (CAR). Subjects taken for the study were children aged 5-6 years in Class B3 consisting of 23 children. Data collection techniques in this study were through observation sheets and documentation. Data analysis technique used to obtain data through the first cycle consisting of 2 meetings and the second cycle consisting of 2 meetings is to use the formula percentage = f / n x100%. The results showed that the development of a child's prayer interest in reading increased from the initial data 59.60% to the implementation of the action in the second cycle of meeting 2 telling stories using varied media in children aged 5-6 years at TK Barokah Pekanbaru by 89.13% and had an increase by 29.53%. The implication of this research is that the teacher must create a fun learning process using the method of telling stories with a variety of media. Therefore the method of storytelling is demonstrated in learning because it is proven to improve the ability to read children's prayer interest and apply it in everyday life.